KYRGYZ SPEECH ETIQUETTE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The culture of behavior is an integral part of human culture; it acts as an externalexpression of the spiritual wealth of the individual, his inner world. This is a set of forms of everydayhuman behavior (in work, everyday life, communication), in them the external expression of themoral and aesthetic norms of his behavior is manifested. They especially highlight the culture ofspeech, the ability to competently, clearly and beautifully express one’s thoughts without usingvulgar expressions, etc.
Keywords: etiquette, tact, politeness, friendliness, communication, bata, tilek.